DETERMINATION OF REDUCING GREENHOUSE GAS EMISSIONS BY MEANS OF RENEWABLE ENERGY SOURCES APPLICATION - Косинчук, О.; Кондратюк, Г.; Козлова, Н.; Новицька, Є. (Science-based technologies, 2010)
The greenhouse gases regulated by the Ciot’s Protocol are mentioned. The methodology for quantitative estimationof greenhouse gases emission in СО2 equivalent is described. The method for long-time СО2 emission estimation proposed by means of renewable energy sources application.